Thematic Analysis of Laxmi Prasad Devkota’s Poem “The Lunatic” - Sharma, Lok Raj (International Research Journal of MMC, 2022)
A literary text can be analyzed through numerous perspectives, and a thematic analysis stands as one of the perennial perspectivespractised in analyzing poetry. This perspective embraces a qualitative research method that is used for exploring and interpreting patterned meaning across datasets. This article makes an effort to explore pertinent themes in Devkota’s tough philosophical poem “The Lunatic”. This articlewriter employs an inductive approach to analyze the poem. The inductive approach involves deriving meaning and creating themes from data without any preconceptions. This article, which makes use of words, phrases and verse lines mustered from the poem as qualitative datasets, winds up with the rebellion against inhumanity as one of the most prominent themes of the poem. This article will be utterly significant to the teachers and the students of literature.